Effect of electric field on Ce doped TiO2: Lattice phase transition, Pd valence distribution and enhancement of methane oxidation activity. (1st March 2022) - Zhao, Xuteng; Wang, Yinan; Zheng, Zuwei; Zhang, Yiran; Chen, Ting; Guo, Dongdong; Cao, Honglin; Zhan, Reggie; Lin, He
Highlights: Electric field induces Ce-TiO2 (Ce/Ti≤0.2) transition from anatase to rutile. Amorphous Ce-Ti structure can remain stable in electric field. Electric field induces reduction of Pd 2+ to Pd 0 . Catalyst with Ce/Ti = 0.1 showed higher catalytic activity in electric field. Abstract: Electric field assisted catalysis is regarded as an emerging approach for methane catalytic oxidation in recent years. In this paper, the catalytic performance of Pd/Ce-Ti nano-catalyst for methane oxidation in an electric field was evaluated. We found appropriate Ce doping with TiO2 lattice structure are beneficial to enhance the catalytic activity (Catalyst with Ce/Ti = 0.1 has 90% CH4 conversion at 256 ℃ with 3 mA current, 30, 000 mL·g −1 ·h −1 ). XRD, Raman, BET, TEM, XPS and H2 -TPR were used to study the surface properties and structure changes of the catalyst in electric field. It was found metallic Pd 0 generation on surface is beneficial to improve the reaction activity and electric field could promote the reduction of Pd 2+ to Pd 0 . For Ce-Ti solid solution, electric field can induce the transformation from anatase to rutile. During the dynamic lattice phase transition, catalytic activity increased significantly in a short time, but the CH4 conversion decreased gradually as the structure became stable. In addition, Ce-Ti amorphous structure has better stability in an electric field.